Sejarah Pemikiran Ekonomi Islam Ibn Khaldun - Zubair, Zubair (Buletin Al-Turas, 2006)
Abdurrahman Abu Zaid Waliuddin ibn Khaldun, well known as IBn Khaldun, was born in Tunisia on Ramadhan 1st, 732 H/May 7, 1332 AD. He is a genious Muslim Scholar at his age in sociology, History, economy (fiqh/Islamic jurisprudence) etc. His expert is well recognized by other scholars both Muslim and non-Muslim.